CONSIDERATIONS REGARDING THE IMPLEMENTATION OF A PERFORMANCE MANAGEMENT SYSTEM IN PRIVATE HOSPITALS - Marian TAICU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2013)
Obtaining performance in private hospitals require a proper management of costs and implementing a situation for performance monitoring. The implementation of a cost calculation method in hospitals is a complex process that must take into account the particularities of the activity in health care system. This paper presents a comparative analysis of four costing methods and a model of performance monitoring situation, adapted to the specific of the hospitals.